Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/ccr3.3345
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and thalassemia beta major in splenectomized patient: Clinical case progression and literature review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It is mainly due to either alpha or beta chains hemoglobin reduction leading to defects that cause a wide range of clinical presentations. Thalassemia can also be categorized into transfusion dependent or independent 6 …”
Section: Discussionmentioning
confidence: 99%
“…It is mainly due to either alpha or beta chains hemoglobin reduction leading to defects that cause a wide range of clinical presentations. Thalassemia can also be categorized into transfusion dependent or independent 6 …”
Section: Discussionmentioning
confidence: 99%
“…Mostly because of the multiple organ involvement which occurs in thalassemia patients due to iron overload and chronic anemia status that affect the heart, lungs, liver, and endocrine glands. Thus, those patients were added to other vulnerable population at risk of COVID-19 infection and complications [6,21] . Also, Previous studies demonstrated that beta thalassemia patients tend to have may changes in their immune system like higher levels of IL-1α, TNF-α and IL-1β, IL-6, IL-8, C-reactive protein, neopterin, reduced C3 level and complement activity.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on this clinical course Thalassemia was categorized into transfusion dependent thalassemia (TDT) and non-transfusion dependent thalassemia (NTDT) [4,5] COVID-19 pandemic was considered to cause a real challenge for haemoglobinopathies patients, their surroundings including families and medical staff as per the statement from Thalassemia international Federation (TIF) which published on the 13th of July 2020 considering patients with hemoglobinopathies at greater risk to get the infection. However, they also emphasized the lack of evidence regarding the clinical course of COVID-19 infections in this category of patients [6] . Here we present a description of two BTM cases infected with COVID-19 in Qatar.…”
Section: Introductionmentioning
confidence: 99%
“…30 From the previous results of studies, some clinical trials started to use HBF inducers agent s in protocols for treatment COVID-19 like Hydroxyurea and Panobinostat 31 . However, some literature and case studies approved that beta-thalassemia patients had a higher risk of COVID-19 complications due to iron overload and splenectomy 32,34 .…”
Section: Role Of Fetal Hemoglobin In Covid-19mentioning
confidence: 99%